(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
The present study aimed to diagnose the competitiveness of Medium Industry, Barquisimeto, Lara State, Venezuela. For which, was framed in a non-experimental design field, qualitative descriptive type and as a tool for gathering the information, a questionnaire was used that integrated theoretical elements for measuring competitiveness through twelve (12) pillars according to global competiveness index and organizational variables used by Zonta (2003). Results showed the current status of SME of Barquisimeto in relation to competitiveness and the perception that its managers have about it.